An Extremely Rare Disorder of Somatic Mosaicism: CLOVES Syndrome. (October 2016) - Anderson, Sharon; Brooks, Susan Sklower
Abstract : Background: CLOVES (Congenital Lipomatous Overgrowth, Vascular malformations, Epidermal nevi Scoliosis, Skeletal, Spinal) syndrome is an extremely rare, complex, non-Mendelian genetic condition with clinical overlap to several other overgrowth syndromes. Purpose: This article shares an interesting case report of the prenatal to postnatal diagnostic course for an infant with this condition. Case Findings/Results: It shares prenatal and postnatal images and imaging studies which helped confirm the diagnosis. In addition, the unusual genetic causes of the condition as well as recommended patient-specific management and treatment therapies for this complex condition are discussed. Implications for Practice: Practice implications include honing of physical examination skills and facilitating diagnostic testing required to differentiate CLOVES syndrome from similar conditions. Providers must provide ongoing information and ensure support to families during this diagnostic process. In addition, the majority of care will likely be provided beyond the newborn period. As such, providers must facilitate outpatient follow-up with a number of consultants after hospital discharge. Implications for Research: Because CLOVES syndrome is so rare, research in this area is limited to a small number of field experts. These experts, however, are well-suited to continue research surrounding disease management and lesion treatment (whether surgical, procedural, or medical) moving forward.